P6: ANTIPLATELET AND ANTICOAGULANT USE IN RANDOMISED TRIALS OF PATIENTS UNDERGOING ENDOVASCULAR INTERVENTION FOR PERIPHERAL ARTERIAL DISEASE: SYSTEMATIC REVIEW. (27th April 2021) - Qureshi, MI; Li, HL; Ambler, GK; Wong, KHF; Dawson, S; Chaplin, K; Cheng, V; Hinchliffe, RJ; Twine, CP
Abstract: Introduction: Guideline recommendations for antithrombotic (antiplatelet and anticoagulant) therapy during and after endovascular intervention are patchy and conflicted, in part due to a lack of evidence. The aim of this systematic review was to examine the antithrombotic specifications in randomised trials for peripheral arterial endovascular intervention. Method: This review was conducted according to PRISMA guidelines. Randomised trials including participants with peripheral arterial disease undergoing endovascular arterial intervention were included. Trial methods were assessed to determine whether an antithrombotic protocol had been specified, its completeness, and the agent(s) prescribed. Antithrombotic protocols were classed as periprocedural (preceding/during intervention), immediate postprocedural (up to 14 days following intervention) and maintenance postprocedural (therapy continuing beyond 14 days). Trials were stratified according to type of intervention. Result: Ninety-four trials were included. Only 29% of trials had complete periprocedural antithrombotic protocols, and 34% had complete post-procedural protocols. In total, 64 different periprocedural protocols, and 51 separate postprocedural protocols were specified. Antiplatelet monotherapy and unfractionated heparin were the most common choices of regimen in the periprocedural setting, and dual antiplatelet therapy (55%) was most commonly utilised postprocedure. There is an increasing tendency to use dual antiplatelet therapy with time or for drug-coated technologies. Conclusion: Randomised trials comparing different types of peripheral endovascular arterial intervention have a high level of heterogeneity in their antithrombotic regimens, and there has been an increasing tendency to use dual antiplatelet therapy over time. Antiplatelet regimes need to be standardised in trials comparing endovascular technologies. Take-home message: To determine the benefits of any endovascular intervention within a randomised trial, antithrombotic regimens should be standardised to prevent confounding. This systematic review demonstrates a high level of heterogeneity of antithrombotic prescribing in randomised trials of endovascular intervention, and an increasing tendency to utilise dual antiplatelet therapy, despite a lack of evidence of benefit, but an increased risk of harm.